Semiconducting metal oxide thin-film transistors - Zhou, Ye (Semiconductor engineer) (IOP (Series). Release 21., 2020)
Semiconducting metal oxide thin-film transistors (TFTs) are promising candidates for functional electronic devices. This reference text covers the latest developments in the field, including the design, materials characteristics, device operation principles, specialised device applications and mechanisms, including the latest semiconducting TFT technologies. The book introduces the concepts and working mechanisms of semiconducting metal oxide TFTs, with a focus on metal oxide thin films that have desirable electrical and optical properties. The relationship between material properties and device performance is analysed, and materials and device challenges, as well as possible strategies, are discussed.